Contemporary Issues in Teacher Education and Training - Goretti , Maria Kaahwa (African Journal of Education,Science and Technology (AJEST), 2014)
Teacher Education has been an important component of education since time immemorial. This is because all societies in the world have always needed teachers to propagate their cultures from one generation to another.. Without quality teachers, there cannot be quality learners. Teacher Education will continue to influence social, political, economical, and technological developments in our world today. Therefore, teacher education and training should be understood in terms of on-going education innovations which answer contemporary issues that impact teacher education nationally and globally. These are: Indigenous teacher education, Change agent, life skills, leading and managing, different cultures, action research, teacher professionalism, globalization, Facilities and resources, information communication system, and conserving environment. Therefore, teacher training should produce ideal teachers who are ready to answer the challenges of the contemporary issues mentioned. The answer is in training teachers, whose curriculum is designed in an integration innovation with multi disciplinary design to produce productive citizens of the world. It is thus recommended that the teacher training programs should be reviewed, teacher professionalism should be emphasized, and support associations and quality assurance mechanism be put in place. In conclusion, societies should make Teacher Education meaningful and productive to the socio-economic realities.